Comparison of the 2021 ESC guideline with the HFA-PEFF and H2FPEF scores in diagnosing heart failure with preserved ejection fraction - Minjae Yoon; Jaewon Oh; Chan Joo Lee; Seok-Min Kang (Scientific Reports)
Abstract The HFA-PEFF and H2FPEF scores were recently proposed to help diagnose heart failure (HF) with preserved ejection fraction (HFpEF). We aimed to evaluate HFpEF prevalence according to the 2021 European Society of Cardiology (ESC) HF guideline and the HFA-PEFF and H2FPEF scores in patients with unexplained dyspnea and to compare the concordance between these three algorithms in diagnosing HFpEF. We analyzed 992 patients with unexplained dyspnea suspected of having HFpEF, who underwent echocardiography, cardiopulmonary exercise testing, and N-terminal pro-brain natriuretic peptide measurement at a single tertiary center. Patients were classified as having confirmed, suspected, or no HFpEF on high, intermediate, or low scores according to HFA-PEFF or H2FPEF. Additionally, patients were classified into three categories according to elevated natriuretic peptide levels and echocardiographic parameters following the 2021 ESC HF guideline. Among the 992 patients included, confirmed prevalence HFpEF ranged from 28.5% (2021 ESC) to 21.1% (HFA-PEFF) and 4.7% (H2FPEF). Significant differences in the prevalence of hypertension, atrial fibrillation, number of antihypertensive medications, natriuretic peptide levels, and echocardiographic parameters of diastolic dysfunction were observed among the three HFpEF groups, with the highest burden in the group defined by the H2FPEF score. Comparing the HFA-PEFF and H2FPEF scores, 40.2% of patients were classified into different likelihood categories for HFpEF depending on the score used. The overlap of patients diagnosed with confirmed HFpEF according to the three algorithms was limited to 3.5%. HFpEF prevalence in patients with unexplained dyspnea varied significantly depending on the algorithm applied.